Digital Access is not Binary: The 5'A's of Technology Access in the Philippines. Issue 4 (8th February 2019) - Roberts, Tony; Hernandez, Kevin
Abstract: Online political participation has been presented as a possible solution to declining levels of trust in traditional politics. However, the most marginalised communities are often the least connected and participate least in digital citizenship programmes. Much existing literature rests on a binary understanding of citizens as being either connected or unconnected. Progress is therefore often understood simply as a process of "connecting the unconnected." This paper presents primary empirical research from the Philippines, which suggests that such binary understandings disguise more than they reveal. We argue that it is descriptively more accurate and more analytically useful to recognise that multiple classes of technology access exist, which limit digital citizenship in multiple ways. Qualitative methods were used to learn from non‐users and the least connected about the barriers to online civic participation that they experience. The 5'A's of Technology Access was employed as a framework to analyse those barriers and reveal the social and economic factors that they reflect, reproduce, and amplify. Findings suggest that nonbinary and nontechnical understandings of the barriers to digital inclusion are essential to any effective attempt to remove the remaining obstacles to genuinely inclusive digital citizenship.